The Use Of Herringbone Technique to Improve Students’ Reading Comprehension - Anis Munzidah Nur Iftitah (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This study aims to improve the student’s reading comprehension, especially detailed information, and the main idea through the herringbone technique. Herringbone is the technique to help students find important information and main ideas in the text by seeking to answer six comprehension questions on a diagram. The method uses CAR with observation, interview, and test. The data is analyzed by describing the observation checklist and using the mean score formula. There are two kinds of tests. Preliminary test and final test. Based on the results of the analysis data, the improvement in reading comprehension through the herringbone technique has improved well. In the first cycle, the average value increases by 14, which in the initial condition, 62 increases to 74 with a percentage of 63%. In the second cycle, the average value increased by 17, which in the initial condition, 74, increased to 79 with a percentage of 84%. Implications and empirical approaches to understanding reading comprehension with the teaching and learning process of reading comprehension. the technique that can improve students’ reading habits. It is also proposed that researchers also deepen by collecting students’ responses on the use of the Herringbone Technique in teaching reading to foster teachers in formulating better lesson plans in using this technique